2022
DOI: 10.3803/enm.2021.1237
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Alpha-1-Adrenergic Receptor Ameliorates Obesity-Induced Cataracts by Activating Glycolysis and Inhibiting Cataract-Inducing Factors

Abstract: Background: Obesity, the prevalence of which is increasing due to the lack of exercise and increased consumption of Westernized diets, induces various complications, including ophthalmic diseases. For example, obesity is involved in the onset of cataracts.Methods: To clarify the effects and mechanisms of midodrine, an α1-adrenergic receptor agonist, in cataracts induced by obesity, we conducted various analytic experiments in Otsuka Long-Evans Tokushima Fatty (OLETF) rats, a rat model of obesity.Results: Midod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Strikingly, Lamivudine was able to significantly reduce fat in an nhr-49 /PPAR mutant background, suggesting the effects of this drug will be applicable as an anti-obesity intervention in people with Metabolic Syndrome. Similarly, when Midodrine is administered to rats, the expression of PPAR was upregulated or activated resulting in a lowering of fat and body weight [ 50 , 51 ]. We also found that worms exposed to Midodrine displayed a reduction in fat content, and in a PPAR mutant background the fat reduction was even more striking.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, Lamivudine was able to significantly reduce fat in an nhr-49 /PPAR mutant background, suggesting the effects of this drug will be applicable as an anti-obesity intervention in people with Metabolic Syndrome. Similarly, when Midodrine is administered to rats, the expression of PPAR was upregulated or activated resulting in a lowering of fat and body weight [ 50 , 51 ]. We also found that worms exposed to Midodrine displayed a reduction in fat content, and in a PPAR mutant background the fat reduction was even more striking.…”
Section: Discussionmentioning
confidence: 99%
“…The current hypothesis is that selective α 1A -AR agonists may be a potential treatment in heart failure [ 54 , 55 ], since chronic α 1B -AR stimulation, as evidenced through transgenic mouse models, appears to be maladaptive by inducing dilated cardiomyopathy [ 29 ] or heart failure [ 37 ]. While α-AR blockers are a current treatment option for heart failure, using α 1A -AR selective agonists may provide potentially greater benefits such as preventing dementia [ 56 ], improving metabolic function and glucose tolerance [ 56 , 57 , 58 ], increasing lifespan with reduce cancer risk [ 59 , 60 ] and reducing inflammation and cataracts [ 58 , 61 ].…”
Section: α 1a -Ar Agonistsmentioning
confidence: 99%